(untitled) (Global Journal of Human-Social Science, 2016)
This paper investigates the most and the least frequently used vocabulary learning strategies (VLSs) among Saudi undergraduate learners, in Najran University, Saudi Arabia. It forms part of a larger study investigating the different uses of VLSs and how they are perceived by Saudi learners studying a range of different majors. The sample consisted of 158 male and female students, who were asked to report their uses of the seventy-five VLSs (which were divided into 12 dimensions) using a five-point Likert scale in which 1 represents "never", 2 represents "rarely", 3 represents "sometimes", 4 represents "often", and 5 represents "always". A questionnaire was used for the purpose of collecting the data, which were subsequently computed and analysed using descriptive statistics. This involved calculating the overall means of all dimensions and ranking them in order, as well as giving the mean values for the most and least used VLSs in order. The results indicated that, in certain situations, learners tend to focus more on the meaning of words in L1 than in L2.